Gestational Outcomes in Patients with Severe Maternal Morbidity Caused by Hypertensive Syndromes - Daisy de Lucena Feitosa Lins Pinheiro; Francisco Edson de Lucena Feitosa; Edward Araujo Júnior; Francisco Herlânio Costa Carvalho (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2020)
Abstract Purpose To evaluate the impact of the presence of criteria for severe maternal morbidity and maternal near miss associated with hypertensive disorders on maternal and perinatal outcomes in a maternity school. Methods The present is a sub-analysis of a larger study involving 27 centers in Brazil that estimated the prevalence of serious maternal morbidity and near miss. It is an analytical and cross-sectional study with a quantitative approach, involving 928 women who were cared for at Maternidade Escola Assis Chateaubriand (MEAC, in Portuguese), Universidade Federal do Ceará (UFC, in Portuguese), from July 2009 to June 2010. The women were diagnosed with near miss according to the World Health Organization (WHO) criteria. The sample was divided into 2 groups: patients with (n = 827) and without hypertension (n = 101). The results were considered statistically significant when p < 0.05. The Pearson chi-squared and Fisher Exact tests were used for the categorical variables, and the Mann-Whitney U test was used for the continuous variables. Results In total, 51 participants with maternal near miss criteria were identified, and 36 of them had hypertensive disorders. Of these, 5 died and were obviously excluded from the near miss final group. In contrast, we observed 867 cases with non-near miss maternal morbidity criteria. During this period, there were 4,617 live births (LBs) in the institution that was studied. Conclusion In the severe morbidity/maternal near miss population, the presence of hypertensive complications was prevalent, constituting a risk factor for both the mother and the fetus.